- Penerapan Sanksi Rehabilitasi Terhadap Pelaku Tindak Pidana Penyalahgunaan Narkotika Golongan I (Putusan Nomor 1016/Pid.Sus/2022/PN.Jkt.Brt) : The Application of Rehabilitation Penalty to the Perpetrators of Class I Narcotics Abuse Crime (Verdict Number 1016/Pid.Sus/2022/PN.Jkt.Brt) - Abizza Aditya Hamdillah El Thamrin; Novi Eko Baskoro (Reformasi Hukum Trisakti, 2024)
Narcotics abusers are said to be victims of narcotics crimes and are placed into rehabilitation, but based on Decision No. 1016/Pid.Sus/2022/PN.Jkt.Brt. the defendant has been proven and determined as a narcotics abuser based on the results of the assessment and evidence which leads to rehabilitation. The formulation of the problem in this article is how the application of rehabilitation sanctions to the perpetrators of class I narcotics abuse in Decision No.1016/Pid.Sus/2022/PN.Jkt.Brt., and the obstacles and efforts in applying rehabilitation sanctions to perpetrators of class I narcotics abuse. This article uses normative juridical research methods, descriptive research nature, data used Secondary data and primary data, data collection using literature study, data analysis using qualitative, drawing conclusions using the deductive method. In the results of this study, Law Number 35 of 2009 concerning Narcotics has regulated the mandatory use of medical rehabilitation, but in practice it does not run according to the Law. The conclusion is that the implementation of rehabilitation for addicts and victims of narcotics abuse by the National Narcotics Board has followed the existing provisions. However, the possibility of shortcomings in the application of these rules remains open